Addressing Uncomfortable Issues: Reflexivity as a Tool for Culturally Safe Practice in Aboriginal and Torres Strait Islander Health - Wilson, Annabelle (The Australian Journal of Indigenous Education, 2014)
It is well recognised that research with Aboriginal communities needs to be ethical, meaningful and useful, in a way that is defined by communities themselves. This article provides an example of how reflexivity, from a number of positions and paradigms, can be used to undertake such research. I used a reflexive journal to document and critically assess the challenges and discomfort I experienced while undertaking research with Aboriginal communities, including uncertainty and feeling in the minority. Reflexivity allowed me to experience a number of key learnings, including: the importance of relationships; the importance of time, transparency and trust in relationships; reciprocity; the importance of listening; a partnership approach; and the impact of Aboriginal culture and past experience. The way in which I redefined my success as a researcher is also explored. In using reflexivity I reached new levels of understanding about myself, which enabled me to alter my practice and therefore change the experiences of those I was working with, ideally towards experiences that were perceived as culturally safe. Using reflexivity also enabled me to identify my position as a White researcher and centralise the needs and perspectives of Aboriginal people in my research. The purpose of this article is to present my own journey, as well as start a dialogue and provide a framework for how others might use reflexivity to become a culturally safe health professional or researcher and centralise the needs and perspectives of Aboriginal people in research and practice.